Multi-wavelength generation of L-band brillouin/erbium fibre laser - Low, Andy L. Y.; Chien, Su Fong; Wong, W. M. (Springer Link, 2003)
In this paper, the operation of the Brillouin/erbium fibre laser (BEFL) in the long wavelength band (L-band or 1565-1625 nm) is experimentally demonstrated. The Stokes frequency is shifted 10 GHz from its Brillouin pump ( BP) from 1598 to 1612 nm for the single wavelength BEFL. Multiple wavelength generation in the BEFL is realised by adding two 3-dB couplers, which are joined in a reverse-S arrangement to take a portion of the generated BEFL signal and re-inject it into the single-mode fibre (SMF) to seed a cascaded BEFL line in the same direction as the first BEFL line. Twenty lines including the anti-Stokes are obtained with a maximum BP and 980-nm pump power of 8.8 and 92 mW, respectively. The L-band BEFL has the potential to be used in future wavelength division multiplexing (WDM) communication system.